The conquest of the Atlantic - Manton, Grenville G. O.
An account of the first transatlantic flight, from Newfoundland to Ireland, undertaken by John Alcock and Arthur Brown Whitten, 14-15 June 1919. Periodical covers have been included with many of the digitized articles whether they relate to them or not. Extra pages not part of the article in question may also be present.